The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1063/1.2005368
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional atom mapping of dopants in Si nanostructures

Abstract: Atom-probe tomography has successfully mapped three-dimensional ͑3D͒ dopant atom distributions in nanoscale volumes of Si subjected to various processing procedures. The 3D evolution of dopants, specifically effects such as dopant clustering and grain-boundary segregation, were analyzed in implanted polycrystalline Si gate contacts and implanted shallow junctions. A cluster of dimensions 2 ϫ 7 ϫ 8 nm 3 and containing 264 B atoms, was identified at the intersection of three poly-Si grains, verifying that anneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 4 publications
0
47
0
Order By: Relevance
“…95,99,100 Lift-out or coupon extraction methods 95 have been used for site-specific specimen preparation of features such as grain boundaries, 99 interphase interfaces, low volume fraction or inhomogeneously distributed phases, coarse precipitates, 101 as well as ionimplanted and subsurface regions. 102 In addition, the FIB may be used as a final step for electropolished specimens to correct electropolishing artifacts and ensure a circular cross section with a smooth taper angle. 103 Generally, the FIB-based methods require a two-stage process.…”
Section: Focused Ion Beam Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…95,99,100 Lift-out or coupon extraction methods 95 have been used for site-specific specimen preparation of features such as grain boundaries, 99 interphase interfaces, low volume fraction or inhomogeneously distributed phases, coarse precipitates, 101 as well as ionimplanted and subsurface regions. 102 In addition, the FIB may be used as a final step for electropolished specimens to correct electropolishing artifacts and ensure a circular cross section with a smooth taper angle. 103 Generally, the FIB-based methods require a two-stage process.…”
Section: Focused Ion Beam Methodsmentioning
confidence: 99%
“…Pulsed-laser APT has been used to map one-, two-, and three-dimensional distributions of boron, arsenic, and phosphorus with high spatial and compositional resolution. Some examples include the observation of arsenic implant profiles in silicon, 102 boron segregated to grain boundaries in polysilicon, 102 and the lateral diffusion profile of boron in a transistor from a source/drain into the gate region.…”
Section: Silicon-based Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…4 (d)) j. A tungsten needle is prepared in the same way as a conventional atom probe sample and an array of silicon micro tips [20,22]. k. The part of the detached sample is welded with the tungsten tip by platinum deposition.…”
Section: Methodsmentioning
confidence: 99%
“…To date, no research of atom-probe examination of crack tips has been reported (with the exception of the one of the samples described in this paper in Cerezo et al (2007)), although there is a growing literature on the application of the FIB to the preparation of site-specific specimens (Thompson et al, 2005(Thompson et al, , 2007a. Additionally, only several TEM images of crack tips have appeared in the literature.…”
Section: Introductionmentioning
confidence: 91%